A H2O2/HBr system – several directions but one choice: oxidation–bromination of secondary alcohols into mono- or dibromo ketones. Issue 50 (10th August 2018) - Nikishin, Gennady I.; Kapustina, Nadezhda I.; Sokova, Liubov L.; Bityukov, Oleg V.; Terent'ev, Alexander O.
Abstract : Convenience of application, multifaceted reactivity, and compliance with green chemistry principles: H2 O2 –HBr(aq) system for preparation of bromo ketones with yields up to 91%. Abstract : In this work we found that a H2 O2 –HBr(aq) system allows synthesis of α-monobromo ketones and α, α′-dibromo ketones from aliphatic and secondary benzylic alcohols with yields up to 91%. It is possible to selectively direct the process toward the formation of mono- or dibromo ketones by varying the amount of hydrogen peroxide and hydrobromic acid. The convenience of application, simple equipment, multifaceted reactivity, and compliance with green chemistry principles make the application of the H2 O2 –HBr(aq) system very attractive in laboratories and industry. The proposed oxidation–bromination process is selective in spite of known properties of ketones to be oxidized by the Baeyer–Villiger reaction or peroxidated with the formation of compounds with the O–O moiety in the presence of hydrogen peroxide and Bronsted acids.